Integration of confucian and islamic wisdom in Madrasa education: Case study of Ma Lianyuan - Yunpeng, Ma; Mohd Yusoff , Mohd Yakub @ Zulkifli (Journal of Islamic, Social, Economics and Development, 2024)
Hans Küng, a leading scholar in comparative religion and inter-civilizational dialogue, posited that "there can be no world peace without religious peace, and the path to religious peace lies in mutual understanding and dialogue". As globalization intensifies and discussions of civilizational clashes escalate, the dialogue between major religious ideologies becomes critical. Within this dialogue, the educational philosophies of religious texts are crucial for the internal transmission of doctrines and external engagement. This paper compares the educational philosophies of the Confucian classic The Analects and the Islamic classic The Quran, incorporating the educational thoughts of Ma Lianyuan, a renowned Hui Confucian educator. It shows that Ma Lianyuan's Islamic madrasa education in Yunnan was significantly influenced by the Confucian Analects. By exploring the convergence of these two educational philosophies in Hui Confucian madrasa education, the study delves into the "spirit of religious commonality" embodied in both systems. Additionally, the research addresses potential negative aspects of this influence, illustrating how integrating Confucian and Islamic educational philosophies can result in both beneficial and problematic cultural assimilation and adaptation. This analysis offers insights into the complex interplay between these rich traditions, emphasizing the importance of comparative religious education in promoting mutual understanding and dialogue.